2006
DOI: 10.2176/nmc.46.438
|View full text |Cite
|
Sign up to set email alerts
|

Distal Anterior Cerebral Artery Mirror Aneurysms and Middle Cerebral Artery Aneurysms-Case Report-

Abstract: Fig. 1 Cranial axial T 1 -weighted magnetic resonance image revealing a mass lesion with surrounding cerebral edema in the left frontal lobe and probable aneurysm formation in the interhemispheric space. AbstractA 52-year-old woman presented with bilateral distal anterior cerebral artery (ACA) mirror aneurysms, in addition to two right middle cerebral artery (MCA) aneurysms. The left distal ACA and right MCA aneurysms were clipped through right interhemispheric and right pterional craniotomies. The right dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The incidence in our series was 8% comparable to other studies. [1][2][3][4] There was female preponderance in our series (57.7%) similar to the literature. 3,9 Mean age of presentation was 55 years.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The incidence in our series was 8% comparable to other studies. [1][2][3][4] There was female preponderance in our series (57.7%) similar to the literature. 3,9 Mean age of presentation was 55 years.…”
Section: Discussionsupporting
confidence: 90%
“…Distal anterior cerebral artery (DACA) aneurysms represent about 1.5% to 9.2% of all aneurysms. [1][2][3][4][5][6][7] Most common location is at the bifurcation of the pericallosal and callosomarginal arteries. Most of the DACA aneurysms are found to be less than 5 mm in diameter, 5 and giant aneurysms are exceedingly rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have compared the clinical features and treatment of MirAn patients, and most of them are case reports 1,4,7,8. To the best of our knowledge, only two other large-scale comparative studies on MirAn have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies are case reports, and they were therefore unable to confirm or refute any hypotheses 1,2,48. Therefore, studies in larger cohorts of MirAn patients are needed to confirm the association between MirAn and its supposed risk factors, since a better understanding of the risk factors associated with MirAn could help with rupture prevention, diagnosis, treatment, and prognosis.…”
Section: Introductionmentioning
confidence: 99%